Trieste, slavic periphery: a question of minority through the slovénitude of Boris Pahor (Colloquia Comparativa Litterarum, 2025)
Torn by ideological and identity stresses (existential ruptures in posse et in esse), Trieste has lived the European tensions looking for an impossible balance between the Austro-Hungarian cosmopolitanism and the affirmation of national cultures. With an application of the centre/margin paradigm, we intend to consider the role of the peripheral literature of this city – namely, the role of the literature of its ethnic minorities, especially the literary production of the Slovene minority. The work of Boris Pahor will help us to particularize the subject of this essay, which aims to grasp the "differential fact" expressing the singularity of the comparative approach.
Keywords: Trieste; minorities; identity; Boris Pahor